SUCCESS AND SAFETY OF MISOPROSTOL FOR TREATMENT OF EARLY PREGNANCY FAILURE - Nazir, Quratulann; Habib, Sadia; Sultana, Ruqqia; Noor, Muhammad Munir; Parveen, Zahida (Journal of Ayub Medical College Abbottabad, 2018)
Background: Early pregnancy failure is a common complication in pregnancies. It can be managed medically as well as surgically. Lately there has been an emphasis on medical management of early pregnancy failure. Misoprostol, a Prostaglandin E1 analogue has been found to be safe and effective in treatment of early pregnancy failure. Methods: This was a descriptive cross-sectional study that was conducted at the department of gynaecology and obstetrics, Ayub teaching hospital Abbottabad from Jan 2015 to Dec 2016. A total of 81 pregnant women with early pregnancy failure were enrolled in the study. Misoprostol was administered in a dose of 800 µg PO and repeated every 3 hours for a maximum of three doses if and when required. Results: Misoprostol was effective in 60 (74.07%) patients and it resulted in complete expulsion of products of conception. The remainder needed surgical evacuation. There was a low incidence of side effects with nausea being the most common (4.94%) followed by PV bleeding (3.70%), abdominal cramps (3.70%) and diarrhoea (2.47%). Conclusion: Misoprostol is a safe and effective treatment option for the management of early pregnancy failure. Keywords: Abortion; Pregnancy failure; Misoprostol